Cruel seduction eaudiobook - Robert, Katee (Dark Olympus, 2023)
Aphrodite has never flinched at getting her perfectly manicured hands dirty, and she's not about to start now—even if that means marrying Olympus's enemy number one, the new Hephaestus. She has a wicked plan to keep her deadly new husband off-balance, seducing the one person he seems to care about most in this world: Pandora, a woman as beautiful as she is sweet. Two can play the seduction game, however, and Hephaestus is all too happy to put his new wife in her place. Her ex, Adonis, seems like he'll do the trick. It doesn't hurt that he's gorgeous in the way of fallen angels either. The only problem with using seduction as a weapon? Hearts are all too quick to get involved. With Hephaestus and Aphrodite trading venomous strikes that feel a whole lot like foreplay, lines become blurred and emotions entangled. But a broken heart may be the least of their worries. With unrest in Olympus reaching new heights, these bedroom games may have deadly consequences for them both, their city, and everyone they've come to love.